2010
DOI: 10.1590/s0100-40422010000100022
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de compostos fenólicos por cromatografia líquida de alta eficiência isocrática durante estacionamento da erva-mate

Abstract: Recebido em 14/2/09; aceito em 9/6/09; publicado na web em 13/11/09 DETERMINATION OF PHENOLIC COMPOUNDS BY ISOCRATIC HIGH PERFORMANCE LIQUID CHROMATOGRAFIC METHOD DURING STORAGE OF YERBA-MATE. Different phenolic compound, 5-caffeoylquinic acid (5-CQA), caffeic acid (AC) and rutin (Ru) contents of yerba-mate (Ilex paraguariensis) Brazilian samples of 06 different regions of São Mateus -Paraná, during natural and accelerated industrial storage, were evaluated. For quantification, a reverse phase HPLC isocratic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
(23 reference statements)
0
15
0
3
Order By: Relevance
“…24 More detailed characterization of iron nanoparticles synthesized using green tea revealed the progressive reduction of Fe 3+ to Fe 2+ during the preparation to form nanoparticles of amorphous nature, while the nanoparticles prepared by the borohydride reduction method were identified as crystalline zero-valent iron nanoparticles. 25 Comparison between the degradation of methylene blue and methyl orange (MO) dyes showed that green iron nanoparticles are more effective as Fenton-like catalyst This work reports the green synthesis of iron nanoparticles by tea extracts of the South America polyphenol-rich plant yerba mate (Ilex paraguariensis); 27 supported in silica gel, a non-expensive, non-toxic, readily available and acid support. The effect of synthesis conditions in the organic and iron content of the catalysts was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…24 More detailed characterization of iron nanoparticles synthesized using green tea revealed the progressive reduction of Fe 3+ to Fe 2+ during the preparation to form nanoparticles of amorphous nature, while the nanoparticles prepared by the borohydride reduction method were identified as crystalline zero-valent iron nanoparticles. 25 Comparison between the degradation of methylene blue and methyl orange (MO) dyes showed that green iron nanoparticles are more effective as Fenton-like catalyst This work reports the green synthesis of iron nanoparticles by tea extracts of the South America polyphenol-rich plant yerba mate (Ilex paraguariensis); 27 supported in silica gel, a non-expensive, non-toxic, readily available and acid support. The effect of synthesis conditions in the organic and iron content of the catalysts was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Saponins, phenolic compounds such as chlorogenic acid and flavonoids, methylxanthines, amino acids, sugars, and vitamins are found in yerba-mate (Jacques et al, 2007;Heck;De Mejia, 2007;Burris et al, 2012). High-performance liquid chromatography has been used to analyze phenolic compounds and methylxanthine in yerba-mate, using mainly a mobile phase gradient (Dutra;Ribani, 2010;Isolabella et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The maté is recognized worldwide for its nutritional and medicinal value being included in several nationals food codes such as the Argentine Food Code, Latin-American Food Code and Pharmacopoeias such as Martindale, British Herbal Pharmacopoeia and German Commission E Monographs (Anesini et al, 2006). Several studies on maté have reported the presence of xanthines such as caffeine and theobromine, saponines, and several phenolic compounds, mainly chlorogenic acids and dicaffeoylquinic acid derivatives (Bravo et al, 2007;Dutra et al, 2010;González de Mejia et al, 2005;Heck et al, 2008;Jaiswal et al, 2010;Markowicz Bastos et al, 2007). It has also been reported that maté extracts have an in vitro antioxidant capacity (AOC) which is due to the presence of chlorogenic acids and dicaffeoylquinic acid derivatives that have an antioxidant capacity equal to or higher than that of ascorbic acid and vitamin E (Bravo et al, 2007;Chandra & Gonzalez de Mejia, 2004).…”
Section: Introductionmentioning
confidence: 99%